Transmission of Nevirapine-Resistant HIV Type 1 via Breast Milk to Infants After Single-Dose Nevirapine in Beira, Mozambique - Micek, Mark A. (Oxford University Press, 2014)
Acquisition of nevirapine (NVP)–resistant human immunodeficiency virus type 1 (HIV-1) by breast-feeding infants after receipt of single-dose NVP to prevent mother-to-child transmission is not well defined. A prospective observational study of 307 infants evaluated the rate of breast milk transmission of NVP-resistant HIV and the concentrations of mutants over time. NVP resistance was detected in 9 of 24 infants (37.5%; 95% confidence interval, 18.8%–59.4%) infected via breast milk. Eight had a pure mutant HIV population at the time infection was first detected, and majority mutant populations persisted in all 6 infants with follow-up specimens. Infection of breast-feeding infants with NVP-resistant HIV resulted in mutants persisting as the dominant virus, which may indefinitely compromise treatment with NVP-based antiretroviral regimens.